2011
DOI: 10.1002/eat.20798
|View full text |Cite
|
Sign up to set email alerts
|

Sodium oxybate in the treatment of binge eating disorder: An open‐label, prospective study

Abstract: In this open-label trial, sodium oxybate was effective in binge eating disorder, but associated with high a discontinuation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…However, individual patients did experience modest losses in weight with the overall group profile indicative of some benefit relative to placebo. Such findings are consistent with an open-label trial in humans (Arima and Oiso, 2010), and research in rats (Patel and Ebenezer 2010), in which baclofen has been reported to reduce body weight, as well as an open-label trial in which sodium oxybate, which also acts as a GABA-B agonist, reduced binge eating and body weight (McElroy et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, individual patients did experience modest losses in weight with the overall group profile indicative of some benefit relative to placebo. Such findings are consistent with an open-label trial in humans (Arima and Oiso, 2010), and research in rats (Patel and Ebenezer 2010), in which baclofen has been reported to reduce body weight, as well as an open-label trial in which sodium oxybate, which also acts as a GABA-B agonist, reduced binge eating and body weight (McElroy et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…In addition to the open-label baclofen trial, results are also consistent with an open-label trial in which sodium oxybate reduced binge frequency (McElroy et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…Reports of weight loss with GHB are less common, although popular use of the drug by body builders during the 1990s was predicated on its ability to release growth hormone, leading to increased lean muscular mass and diminished body fat (Fuller et al 2004). Indeed, patients treated chronically with GHB for narcolepsy show loss of body weight over time (Husain et al 2009) and a recent open-label trial found GHB to be efficacious in promoting appetite control and body weight loss in people suffering from binge eating disorders (McElroy et al 2010). The present study is, to our knowledge, the first report of chronic GHB-induced body weight loss in rats and it is interesting to note that this effect tended to persist for several weeks following cessation of GHB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These associations were not related to the presence of other sleep disorders nor to current pharmacological treatment, although we cannot rule out an effect of the NC medications. Previous studies, however, have shown that modafinil, venlafaxine, and sodium oxybate decrease food intake/ craving, [38][39][40] suggesting that these treatments could have mitigated these abnormal nocturnal behaviors.…”
Section: Demographic Features Sleep Comorbidity and Psychological Tmentioning
confidence: 95%